Mandibular adenomatoid odontogenic tumor: A report of an unusual case - Raman Preet Kaur Bhullar; Ramandeep S Brar; Simarpreet Virk Sandhu; Himanta Bansal; Rajat Bhandari (Wolters Kluwer Medknow Publications, 2011)
Adenomatoid odontogenic tumor (AOT) is a slow-growing, benign tumor that appears in the anterior portion of the jaws and more frequently, the anterior maxilla usually in association with the crowns of unerupted teeth. Most of the tumors are diagnosed in second decade of life. A rare case report of AOT associated with an impacted right mandibular first premolar in a 24-year-old female is reported.